Methodological choices for research in Information Science: Contributions to domain analysis - Freitas, Juliana Lazzarotto [UNESP]; Bufrem, Leilah Santiago [UNESP]; Breda, Sonia Maria (Pontificia Universidade Catolica Campinas, 2016)
The article focuses on the ways of organizing studies according to their methodological choices in the Base Referencial de Artigos de Periodicos em Ciencia da Informacao (Reference Database of Journal articles in Information Science). We highlight how the organization of scientific production by the methodological choices in Information Science contributes to the identification of its production features and domain analysis. We studied research categories and proposed five classification criteria: research purposes, approaches, focus, techniques and type of analysis. The proposal of a corpus in Information Science is empirically applied, represented by 689 articles, 10% of the production indexed in Base Referencial de Artigos de Periodicos em Ciencia da Informacao from 1972 to 2010. We adopt content analysis to interpret the methodological choices of authors identified in the corpus. The results point out that exploratory studies are more predominant when considering the research purpose; regarding the research approach, bibliographic and documentary studies are more predominant; systematic observation, questionnaire and interview were the most widely used techniques; document analysis and content analysis are the most widely used types of analysis; the research focus of theoretical, historical and bibliometric studies are more predominant. We found that some studies use two methodological choices and explicit epistemological approaches, such as the studies following the positivist approach in the 1970s, and those influenced by the phenomenological approach in the 1980s, which increased the use of methods in qualitative research.
Keywords: Brapci; Database; Information Science; Methodological choices; Scientific methodology